Targeted therapy of underlying conditions improves sinus rhythm maintenance in patients with persistent atrial fibrillation: results of the RACE 3 trial. (1st February 2018) - Rienstra, Michiel; Hobbelt, Anne H; Alings, Marco; Tijssen, Jan G P; Smit, Marcelle D; Brügemann, Johan; Geelhoed, Bastiaan; Tieleman, Robert G; Hillege, Hans L; Tukkie, Raymond; Van Veldhuisen, Dirk J; Crijns, Harry J G M; et al.
Abstract: Aims: Atrial fibrillation (AF) is a progressive disease. Targeted therapy of underlying conditions refers to interventions aiming to modify risk factors in order to prevent AF. We hypothesised that targeted therapy of underlying conditions improves sinus rhythm maintenance in patients with persistent AF. Methods and results: We randomized patients with early persistent AF and mild-to-moderate heart failure (HF) to targeted therapy of underlying conditions or conventional therapy. Both groups received causal treatment of AF and HF, and rhythm control therapy. In the intervention group, on top of that, four therapies were started: (i) mineralocorticoid receptor antagonists (MRAs), (ii) statins, (iii) angiotensin converting enzyme inhibitors and/or receptor blockers, and (iv) cardiac rehabilitation including physical activity, dietary restrictions, and counselling. The primary endpoint was sinus rhythm at 1 year during 7 days of Holter monitoring. Of 245 patients, 119 were randomized to targeted and 126 to conventional therapy. The intervention led to a contrast in MRA (101 [85%] vs. 5 [4%] patients, P  < 0.001) and statin use (111 [93%] vs. 61 [48%], P  < 0.001). Angiotensin converting enzyme inhibitors/angiotensin receptor blockers were not different. Cardiac rehabilitation was completed in 109 (92%) patients. Underlying conditions were more successfully treated in the intervention group. At 1 year, sinus rhythm was present in 89 (75%) patients in the intervention vs. 79 (63%) in the conventional group (odds ratio 1.765, lower limit of 95% confidence interval 1.021, P  = 0.042). Conclusions: RACE 3 confirms that targeted therapy of underlying conditions improves sinus rhythm maintenance in patients with persistent AF. Trial Registration number: Clinicaltrials.gov NCT00877643.